Correlation between Folate Intake during Pregnancy and Preterm Labor in Mothers with 0-9 Months Old Babies - Gufi George Stefanus; Siti Nur Fatimah; Eppy Darmadi Achmad (Althea Medical Journal, 2015)
Background: Nutritional factors such as folate intake are important during pregnancy. Satisfying nutritional needs of pregnant mothers is necessary to avoid complications during pregnancy such as preterm labor, High infant mortality rate in Indonesia is still high. This study  aimed to study the relationship between folate intake during pregnancy and preterm labor.  Methods: This study used a cross-sectional analytic approach by using semi-quantitative Food Frequency Questionnaire, as an instrument on mothers with 0−9 months old babies living in the villages of Sayang and Hegarmanah, Jatinangor, Sumedang, Indonesia. Results:  Ninety mothers participated in this study. The result indicated that 25.55% respondents had low folate intake and high incidence of preterm labor (16.67%). Significant association was found between folate intake during pregnancy and preterm labor (p=0.019). Maternal age was not a confounding factor in this study. Conclusions: There is an association between folate intake during pregnancy and preterm labor in mothers living in the villages of Sayang and Hegarmanah, Jatinangor, Sumedang, Indonesia.Keywords: Babies 0−9 months, folate, preterm laborDOI: 10.15850/amj.v2n1.431